KANDUNGAN VITAMIN B6, B9, B12 DAN E BEBERAPA JENIS DAGING, TELUR, IKAN DAN UDANG LAUT DI BOGOR DAN SEKITARNYA (VITAMIN B6, B9, B12 AND E CONTENT OF SEVERAL TYPES OF MEATS, EGGS, FISHES AND MARINE SHRIMPS IN BOGOR AND SURROUNDING AREAS) - Heru Yuniati; Almasyhuri Almasyhuri (Penelitian Gizi dan Makanan (The Journal of Nutrition and Food Research), 2012)
ABSTRACT Food Composition Table (DKBM) in Indonesia has not mentioned all types of nutrients available in the food, particularly vitamin B6, B9 (folic acid), B12, and vitamin E. Therefore this study aimed to analyze the content of vitamin B6, B9 (folic acid), B12, and vitamin E in several types of meat, eggs, fish and marine shrimps consumed in Bogor and surrounding areas. Vitamin B6, B9, B12, and vitamin E from three kinds of meat (chicken, beef, lamb), two types of eggs (chicken, duck), and four species of fish (snapper, bloating, carp and tuna) and crayfish are analyzed using High-Performance Liquid Chromatography (HPLC). The samples used are raw and taken from three locations in Bogor and surrounding areas. Fishes, meats and eggs contain high levels of folic acid, however the amount of folic acid content in meat varies depending on which part of meat the samples are taken, types of organ, and the fat content of the meat. The folic acid content in chicken wings is different with those in thigh. In fatty mutton the folic acid is higher than in those lean meat, and in yolk is higher than those in egg white. Vitamin E content of snapper is the highest amongs other types of fishes (6.54 µg/100 g).Chicken eggs contain a higher amount of vitamin E than duck eggs, while the yolk contains ahigher amount of vitamin E than those egg white. Keywords: animal foods, vitamin B6, vitamin B9 (folic Acid), vitamin B12, vitamin E   ABSTRAK Daftar Komposisi Bahan Makanan (DKBM) yang ada di Indonesia belum memuat semua jenis zat gizi dalam makanan, khususnya vitamin B6, B9 (asam folat), B12 dan vitamin E. Menganalisis kandungan vitamin B6, B9 (asam folat), B12, dan vitamin E dalam beberapa jenis daging, telur, ikan dan udang laut yang dikonsumsi masyarakat di Bogor dan sekitarnya. Kandungan vitamin B6, B9, B12 dan vitamin E dari tiga jenis daging (ayam, sapi, kambing), dua jenis telur (ayam, itik), serta empat jenis ikan (kakap, kembung, mas, tongkol) dan udang laut dianalisis dengan High-Performance Liquid Chromatography (HPLC). Sampel yang digunakan adalah bahan mentah, yang diambil dari 3 lokasi di Bogor dan sekitarnya. Ikan, daging dan telur mengandung tinggi asam folat, yang besarnya bervariasi tergantung pada bagian bahan makanan. Jumlah asam folat di dalam sayap ayam berbeda dengan di dalam paha, dalam daging kambing berlemak sedikit lebih tinggi dibandingkan dengan di dalam daging tanpa lemak. Jumlah asam folat dalam kuning telur juga lebih tinggi dibandingkan dengan di dalam bagian putih telur. Kandungan vitamin E ikan kakap  paling tinggi dibandingkan dengan ikan lainnya (6,54 µg/100 g). Telur ayam mengandung vitamin lebih tinggi dibandingkan dengan telur itik, demikian pula bagian kuning telur lebih tinggi daripada bagian putih telur. [Penel Gizi Makan 2012, 35(1): 78-89] Kata kunci: makanan hewani, asam folat, vitamin B6, vitamin B12, vitamin E